PROPERTIES OF TWO REGULATING GENES FOR ALKALINE PHOSPHATASE - Garen, A. (1962)
Garen, A. (University of Pennsylvania, Philadelphia) and H. Echols. Properties of two regulating genes for alkaline phosphatase. J. Bacteriol. 83:297–300. 1962.—A constitutive mutation in one of the two regulating genes for alkaline phosphatase has two effects on the synthesis of the enzyme: repression of synthesis is blocked, and the cell's capacity to produce the enzyme is reduced. The behavior of this type of mutation has been studied in heterozygotes. The results suggest that the product of this regulating gene functions as an inducer as well as a repressor.